A chromaticity-tunable white LED by screen-printing red phosphor coating on PiG plates. Issue 16 (December 2016) - Xiang, Run; Liang, Xiaojuan; Xi, Qiaoya; Yuan, Zhanfei; Chen, Cirui; Xiang, Weidong
Abstract: Currently, phosphor-in-glass (PiG) approach draws great attention because of its excellent thermal resistance and facile process in w-LED fabrication. However, the absence of red emissive component results in poor chromaticity quality, which greatly restricts its application in the high-quality indoor lighting. In the present work, a transparent garnet-based PiG was successfully prepared by introducing the Y3 Al4.5 Ga0.5 O12 :Ce 3+ (YAGG) green phosphor into TeO2 -based glass matrix, and we demonstrated the possibility offered by the screen-printing technique for warm w-LED applications by coupling the PiG plate stacked with a red phosphor coating on commercial InGaN LED. The microstructures and luminescent properties of them were investigated in detail. After simply varying the red phosphor concentration as well as the YAGG PiG thickness, a facile chromaticity tuning for the thus-fabricated LED was achieved in the range changing from cool white to warm white. Moreover, this developed luminescent material presented an excellent heat-resistance performance. Hopefully, the red phosphor coated PiG color converter is applicable in the long-lifetime high-power color-tunable w-LEDs.